Multistage Stimulus‐Responsive Room Temperature Phosphorescence Based on Host–Guest Doping Systems. (6th August 2021) - Tian, Yu; Yang, Jie; Liu, Zhenjiang; Gao, Mingxue; Li, Xiaoning; Che, Weilong; Fang, Manman; Li, Zhen
Abstract: Compared with inorganic long‐lasting luminescent materials, organic room temperature phosphorescent (RTP) ones show several advantages, such as flexibility, transparency, solubility and color adjustability. However, organic RTP materials close to commercialization are still to be developed. In this work, we developed a new host–guest doping system with stimulus‐responsive RTP characteristics, in which triphenylphosphine oxide (OPph3 ) acted host and benzo(dibenzo)phenothiazine dioxide derivatives as guests. Turn‐on RTP effect was realized by mixing them together through co‐crystallization or grinding, in which the efficient energy transfer from host to guest and the strong intersystem crossing (ISC) ability of the guest have played significant role. Further on, multistage stimulus‐responsive RTP characteristics from grinding to chemical stimulus were achieved via introducing pyridine group into the guest molecule. In addition, the anti‐counterfeiting printings were realized for these materials through various methods, including stylus printing, thermal printing and inkjet printing, which brings RTP materials closer to commercialization. Abstract : The influence of different conjugation degrees on the quantum yield and lifetime of room temperature phosphorescence in a host–guest system is discussed. Multistage stimulus‐responsive RTP characteristics from grinding to chemical stimulus were achieved by introducing a pyridine group into the guest molecule. Anti‐counterfeiting printings were realized through various methods, including stylus printing, thermal printing and inkjet printing.